Hegel em diálogo : lógica, história e necessidade - Peralta, Carlo Paim (2022)
The present dissertation has two main objectives, the first being the characterization of speculative logic and the identification of two of the main general requirements that Hegel understood that it must satisfy, namely, immanently providing its own justification, and agreeing with actuality and experience. For this, it was also necessary to clarify some aspects of the relationship between speculative logic and the history of philosophy, such as the parallelism between logical categories and the systems of philosophy. The second objective, on the other hand, consists in the exposition of Hegel's lectures on Spinoza's and Leibniz-Wolff's systems and, finally, in the analysis of the dialectic of modalities, trying to make explicit the dialogue implied therein with these philosophies. As a result, we hope to have contributed to greater clarity regarding the topics addressed and, consequently, the entirety of Hegel’s system.